Inklusi Keuangan Digital Bagi Petani Perempuan Di Wajo: Sebuah Studi Grounded Theory - Amin, Andi Mustika (PT Maju Malaqbi Makkarana, 2025)
The study examines how women farmers in Wajo are adopting digital financial services through a grounded theory approach, focusing on the social, moral, and structural dynamics that shape their financial inclusion practices. Data were collected over five months in 2023 through in-depth interviews, participant observations, and document analysis in three purposively selected villages and then deepened through theoretical sampling. The analysis resulted in four main categories-Instrumental Necessity, Mediated Trust, Moral-Economic Calculus, and Structural Gateways—that collectively build a core process titled “Relational Mediation of Digital Finance.